2003
DOI: 10.1074/jbc.m212458200
|View full text |Cite
|
Sign up to set email alerts
|

The mmaA2 Gene of Mycobacterium tuberculosis Encodes the Distal Cyclopropane Synthase of the α-Mycolic Acid

Abstract: Infection with Mycobacterium tuberculosis (Mtb) remains a severe global health problem that has prompted an aggressive search for new antibiotic targets and vaccine strategies for this persistent pathogen. Recently, a wide variety of genetic determinants of Mtb pathogenicity have been identified, including several genes involved in the biogenesis of the complex Mtb cell envelope. Among these are the mycolic acid cyclopropane synthases, a family of proteins that modify the major cell envelope lipids of Mtb with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 24 publications
2
76
0
3
Order By: Relevance
“…Examples of these are PcaA and MmaA2 mutants that express mycolic acids without α-mycolate cyclopropanation [10,11], CmaA2 mutants that are unable to effect trans-cyclopropanation in the oxygenated mycolates [12], or MmaA4 and MmaA3 mutants that produce mycolic acids without distal functionality of the oxygenated mycolates [13,14]. The significance of secreted free mycolic acids as potential role players in the manifestation of tuberculosis was recently noted when Ojha et al (2008) [15] demonstrated their role in biofilm formation during in vitro growth of M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these are PcaA and MmaA2 mutants that express mycolic acids without α-mycolate cyclopropanation [10,11], CmaA2 mutants that are unable to effect trans-cyclopropanation in the oxygenated mycolates [12], or MmaA4 and MmaA3 mutants that produce mycolic acids without distal functionality of the oxygenated mycolates [13,14]. The significance of secreted free mycolic acids as potential role players in the manifestation of tuberculosis was recently noted when Ojha et al (2008) [15] demonstrated their role in biofilm formation during in vitro growth of M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ligase Gene Disruptions in M. tuberculosis-Gene disruption was performed by specialized transduction of lig::hyg R cassettes using temperature-sensitive mycobacteriophages as described previously (19,20). The lig⌬::hyg R gene disruption cassettes were constructed by PCR amplifying genomic DNA segments flanking each ligase gene and inserting them on either side of the hygromycin resistance gene in plasmid pJSC407, a cloning vector containing the hyg R marker, a cos site, and a unique PacI restriction site for packaging into phAE87.…”
Section: Methodsmentioning
confidence: 99%
“…The lig⌬ knockout cassettes containing the hyg R marker flanked by upstream and downstream M. tuberculosis genomic DNA for each lig locus were packaged into a temperature-sensitive derivative of the mycobacteriophage TM4 and the recombinant phages were then used to transduce M. tuberculosis Erdman to hygromycin resistance (19,20). Southern hybridization of restriction endonuclease-digested genomic DNA from hygromycin-resistant transductants revealed the predicted fragment sizes for correctly targeted allelic exchange at the ligB, ligC, and ligD loci (data not shown).…”
Section: Characterization Of M Tuberculosis Ligd-m Tuberculosis Ligmentioning
confidence: 99%
“…The cyclopropane moiety of mycolic acids is a unique lipid structure that greatly affects the pathogenesis of M. tuberculosis (15). The bacterium uses a family of Sadenosylmethionine-dependent methyltransferases to modify the mycolic acids of its cell envelope with a variety of stereochemistries and positions for cyclopropyl groups (13). There are at least three mycolic acid cyclopropane synthases (PcaA, CmaA1, and CmaA2) that are responsible for these sitespecific modifications of mycolic acids (17).…”
Section: Discussionmentioning
confidence: 99%